Implementasi Metode Caesar Cipher dalam Penerapan Sistem E-Voting Berbasis Web pada Pemilihan Abang None Jakarta - Radithya Pramuditha Yenadi; Fauziah Fauziah; Deny Hidayatullah (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
In this increasingly modern era, technology has become a must in improving performance in every organization and various other activities. One example of the application of technology that will be explained in this research is the design of a web-based e-voting system in the election of Abang None Jakarta by inserting an E-KTP numbers to be able to cast a vote in the election. Previously, the selection of Abang None Jakarta still uses SMS voting system that is considered to be less effective because the use of credits is considered more wasteful than the use of internet quota. In developing this web-based e-voting system, the researcher uses the SDLC (System Development Life Cycle) method and the Caesar Cipher algorithm method for voter data security. Besides that, the Gateaway SMS system is used to prevent any voter who uses someone else's E-KTP before casting a vote in an election. The e-voting system is made using the PHP and Xampp programming languages as its database. The e-voting system is expected to be used in making a transparent decision, speeding up the voting counting process, saving costs and preventing fraud when implementing e-voting in the election of Abang None Jakarta. The results of research is proven successful in terms of both the use of the web to conduct the election and the use of security in encryption and decryption of user data.